DOMAIN-DRIVEN NATIVIZATION: HOW SCIENCE, TECHNOLOGY, AND DAILY LIFE ACCELERATE LOANWORD INTEGRATION IN ENGLISH - Jumamuratova Rahimaxon (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article examines how domain-specific contexts — namely science, technology, and everyday life — accelerate the nativization of loanwords in English, focusing on phonological, morphological, and semantic adaptation mechanisms and their domain-conditioned variation.